The spirit of populism political theologies in polarized times - Schmiedel, Ulrich 1985-; Ralston, Joshua ca. 20./21. Jh (Brill, 2022)
Introduction : political theology in the spirit of populism : methods and metaphors / Ulrich Schmiedel -- Anger : a secularized theological concept / Vincent Lloyd -- "Just because you're paranoid doesn't mean they're not after you" : populism, political theology, and the culturally repugnant other / Thomas Lynch -- The politics of belonging in the nation state : reclaiming Christianity from populism / Mariëtta van der Tol -- America transcendent / Elizabeth Shakman Hurd -- Sacred scripts of populism : scripture-practices in the European far right / Hannah Strømmen -- Hermeneutics, politics, and liberalism in Islamic modernity : beyond populism / Fatima Tofighi -- "If I forget thee, o Jerusalem" : Zionism and the politics of collective memory / Brian Klugvi Contents -- Populism, Christianity, and the role of the theologian / Mattias Martinson -- From incarnation to identity : the theological background of national-populist politics in the western Balkans / Zoran Grozdanov -- Querying populism by queering Chantal Mouffe : understanding hetero-patriarchal populism / Ludger Viefhues-Bailey -- The persistence of white Christian patriarchy in a time of right-wing populism / Esther McIntosh -- The God of the Brexiteers / Lukas Meyer -- Discipling populism : a theopolitical alternative to denial or demonizing / Doug Gay -- A political theology of 'the people' : enlisting classical concepts for contemporary critique / Jonathan Chaplin -- Can Jewish ethics speak to sovereignty? / Julie E. Cooper -- Confessing Christ in 'Christian Europe' : the death of the church as a theological response to populism / Joseph Sverker -- The other in the ecclesial self : the church and the populist challenge / Sturla J. Stålsett -- The orthodox 'unorthodox' : from populism to pluralism / Ryszard Bobrowicz and Johanna Gustafsson Lundberg -- Conclusion : an invitation to comparative political theology / Joshua Ralston
Literaturangaben
Keywords: Politische Theologie; Populismus; Populism / Religious aspects; Populism / Europe; Populism / United States; Political theology / Great Britain; Political theology / United STates; Aufsatzsammlung